2021
DOI: 10.1016/j.scitotenv.2020.144148
|View full text |Cite
|
Sign up to set email alerts
|

Global association between satellite-derived nitrogen dioxide (NO2) and lockdown policies under the COVID-19 pandemic

Abstract: The COVID-19 pandemic has severely affected various aspects of life, at different levels and in different countries on almost every continent. In response, many countries have closed their borders and imposed lockdown policies, possibly bringing benefits to people's health with significantly less emission from air pollutants. Currently, most studies or reports are based on local observations at the city or country level. There remains a lack of systematic understanding of the impacts of different lockdown poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 31 publications
1
29
0
2
Order By: Relevance
“…Of the included studies, nine used quasi-experimental designs, including eight interrupted time series studies 33–40 and one difference-in-difference study. 41 We also identified two observational studies, 42 , 43 two mathematical modelling studies, 44 , 45 six qualitative studies 46–51 and four mixed methods studies. 52–55 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the included studies, nine used quasi-experimental designs, including eight interrupted time series studies 33–40 and one difference-in-difference study. 41 We also identified two observational studies, 42 , 43 two mathematical modelling studies, 44 , 45 six qualitative studies 46–51 and four mixed methods studies. 52–55 …”
Section: Resultsmentioning
confidence: 99%
“… 33 , 36 , 37 , 46 , 49 , 50 Eight studies analysed the effects of international travel measures implemented by multiple countries. 35 , 38–41 , 44 , 45 , 55 Three studies did not focus on specific countries or settings. 34 , 42 , 43 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous studies have shown improvements in air pollution during the lockdown period, these changes measured during the lockdown period could not represent the effect of the lockdown well because of confounders such as secular trends and weather influences [7,8]. Previous studies have assessed the health effects associated with air pollution during the Asia-Pacific Economic Cooperation (APEC) [9] and the 2015 China large-scale military parade periods [10], and one possible problem faced in these studies, as well as recent studies [11,12] during COVID, is a bias against the real effects of policies on air pollutants.…”
Section: Introductionmentioning
confidence: 99%